Inventarisasi Serangga Hama dan Predator pada Pertanaman Kacang Panjang (Vigna sinensis L.) di Kabupaten Ogan Ilir, Sumatera Selatan - Hidayat, Ginanjar Wahyu; Romansah, Evi; Andriyani, Laja; Kusuma, Maghfira Widya; Kusuma, Muhammad Luthfi; Thosin, Thosin; Umayah, Abu; Gunawan, Bambang; Arsi, Arsi (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2022)
Hidayat WH, Romansah E , Andriyani L, Kusuma MW, Kusuma ML, Thosin T, Umayah A, Gunawan B, Arsi A. 2022. Inventory of pest insects and predatory insects in long beans crops (Vigna sinensis L.) in Ogan Ilir District, South Sumatera. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-10 Tahun 2022, Palembang 27 Oktober 2022. pp. 414-422. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Pest control on long bean plants by utilizing natural enemies is part of a control method that emphasizes ecological aspects that are safe and recommended. This study aimed to determine the presence and availability of insect pests and predatory insects in long bean plantations. The types of traps used in this study were Pitfall Trap, Yellow Trap, and Sweep Net. Observations and sampling were carried out in the vegetative phase of long bean plants in three villages: Tanjung Seteko, Tanjung Pering and Permata Villages. Then, the trapped insects were put into vials that had been given 70% alcohol and identified using identification guidebooks and journals. Based on the results of the research, the insect pests found were Agelastica alni, Aphis craccivora, Aulocophora similis, Aulacophora femoralis, Bactrocera triyoni, Bactrocera dorsalis, Nezara viridula, Proxys punctulatus, Riptortus linearis, Sehirus cenctus, Spodoptera litoralis, Maruca vitrata, Brachyplatys subaeneus, Dissosteira carolina. While the predatory insects found were Coccinella transversalis, Pantala flavescens, Proctacanthus milbertii, Stagmomantis carolina, Anax parthenope, Odontoponera denticulate and Oecophylla smaradigna. The highest number of insects obtained were from pests with a total of 14 species with the most from the order Hemiptera. Thus, the availability of insect pests and predators in long bean plantations is different because farmers apply synthetic insecticides so that pest insect species dominate. Based on the observations and analysis of the results, the authors suggest that this research can be redeveloped by making observations in two phases, namely the vegetative and generative phases.